Radical other: living In transition - Nyamupanedengu, Ruvimbo (My University, 2022)
A mental illness unravels only within a social space that in turn explains its form regardless of whether that mental illness was initially related to neurological difficulties. The form adopted by a mental illness is dictatedby the structure of relations in which an individual is capable or unable to participate and therefore by external institutional and social forces. The treatment of individuals whose behavior deviates from what society perceives as ideal is not about their ‘misconduct’ but about conserving our society from falling below the minimum level of decency. Contemporary society struggles to handle social disorders in an organic way so it creates spaces where deviation can be managed such as prisons, psychiatric hospitals and care homes- heterotopias of deviation. Deviants, the structures they inhabit and the landscapes in which these structures exists are treated as the other- an isolated part of society. ‘Munhu munhu nekuda kwevanhu’ means a person is a person through other people. We are not fully human until others make us human. The primary research focuses on how society deals with individuals who are mentally ill. It looks at the impact of social and cultural factors on the development of mental illnesses. Today, the existence of individual Zimbabweans is characterized by the experience of varied nervous conditions. Zimbabwe has become a place of nervous conditions. The impact of approximately two decades of 12 socioeconomic and political instability has had an overwhelming mental, emotional and physical toll on the majority of Zimbabweans who can no longer cope with the hardships of the meltdown. The project seeks to understand the definition and the experience of nervous conditions through a multiplicity of spatial, social, cultural, political and historical constructs. This is done in order to comprehend the development of mental disorders, the spatial response to mental disorders and the influence of society through different layers. Ultimately the intervention attempts to explore how the space between community and the Radical Other can be reconstructed from a tensional line into a transformative space that facilitates the integration of two groups in society that are traditionally perceived as disjointed. The project aims to create a structure and landscape that offers alternative treatment for mental illnesses of different intensities which result from cultural, political, historical and everyday nervous conditions while fostering constructive interactions between patients and the community
A research report is submitted in partial fulfillment for the degree for Master of Architecture (Professional) to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, Johannesburg, 2022